UPAYA PEMERINTAH DESA DALAM MENINGKATKAN PENDAPATAN ASLI DESA (PAD) DI DESA JERORA I KECAMATAN SINTANG KABUPATEN SINTANG - Antonius Erwandi (Universitas Kapuas Sintang, 2018)
The Village Government has the authority to increase Village Original Income (PADes). Village Original Revenue is also an indicator in determining development programs in the village. Increasing the Village Original Revenue (PADes) is carried out through a development planning strategy at the village level which then becomes a regional development program.